A Profile of Farmers and Other Employed Canadians With Chronic Back Pain: A Population‐Based Analysis of the 2009‐2010 Canadian Community Health Surveys. Issue 3 (1st February 2014) - Trask, Catherine; Bath, Brenna; McCrosky, Jesse; Lawson, Josh
Abstract Purpose Chronic back disorders (CBDs) are a serious public health issue, both in the general population and among farmers. However, it is not clear whether all individuals with CBD should be treated the same, or if some subpopulations have special needs. This study's purpose was to determine the demographic, socioeconomic, co‐morbidity, and other health characteristics of Canadian farmers and nonfarmers with self‐reported CBD. Methods We performed a secondary analysis of the 2009‐2010 Canadian Community Health Survey to develop a profile of adults with CBD comparing farmers (N = 350) to nonfarmer employed persons (N = 11, 251). In addition to descriptive analysis, multiple logistic regression was used to control for possible confounding. Findings Our results indicate that farmers with CBD are significantly more likely to be older, less educated, and more often male and living rurally than nonfarmers with CBD. We found no difference between rates and type of co‐morbidities between farmers and nonfarmers. However, the sociodemographic differences between farmers and nonfarmers with CBD may impact the design of effective interventions and have implications for health services planning and health care delivery. The information presented is anticipated to help address the identified need for musculoskeletal disorder prevention in agriculture.